D. I. Baghaliy’s Activity in Kharkiv During the Denikin Regime - Потоцький, В’ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article considers the short period of outstanding Ukrainian historian D. I. Bagaliy’s life, when he was in Kharkov from September1919 to December 1919. At that time the city was under the authority of the Volunteer Army of General Denikin, who tried to pursue a policy of restoring pre-revolutionary order. The article draws attention to the reasons of Dmitry Ivanovich’s move from Kiev to Kharkov, the peculiarities of Bagaliy’s working at the historical-philological faculty of Kharkov University, as well as his scientific and publishing activities.